UiO-66 and ZIF-8 Metal-organic Frameworks for Acenaphthene Adsorption - Zango, Z.U. (Springer Science and Business Media B.V., 2021)
Comparative adsorption of acenaphthene onto UiO-66 and ZIF-8 metal-organic frameworks (MOFs) were investigated. Response surface methodology (RSM) was employed for the process optimizations according to the central composite design (CCD) with 5 inputs variables. The adsorption efficiency achieved were 99.7 and 60.7 for the UiO-66 and ZIF-8, respectively according to the RSM optimization conditions. The model was significantly described according to statistical analysis of variance (ANOVA). The adsorption process was well fitted by pseudo-second order kinetic model with R2 values of 0.9947 and 0.97780 for the UiO-66 and ZIF-8, respectively. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.